2017
DOI: 10.15296/ijwhr.2017.03
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abstinence and Sperm Quality

Abstract: Background: Previous research has documented that sexual abstinence can improve sperm quality. Sexologists have reported that sperms stored in a latex condom decrease at a rate of 60% per minute. Objective: The objective of the current review is to explore the relationship between sexual abstinence duration and other factors that affect standard and substandard semen production. Design: A scientific review of published literature. Main Outcome Measure: Specific focus is to discuss how sexual abstinence behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated the association of progressive motility and between abstinence time and motility, with peak progressive motility noted after abstinence of 3 days or less. [ 25 26 ] Furthermore, studies have identified an association between abstinence time and morphology with no clear consensus. [ 27 ] Few studies also shown an impact of abstinence time on DNA fragmentation rates, which was lower with shorter abstinence period and worsened with longer abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the association of progressive motility and between abstinence time and motility, with peak progressive motility noted after abstinence of 3 days or less. [ 25 26 ] Furthermore, studies have identified an association between abstinence time and morphology with no clear consensus. [ 27 ] Few studies also shown an impact of abstinence time on DNA fragmentation rates, which was lower with shorter abstinence period and worsened with longer abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed semen parameters reduced significantly after an abstinence of 4 30 , 18 39 , 24 19,28,40 or 36 hours of collection 39 . Abstinence advised by different authors differed from 2 39 , 3 41 , 3-5 19,41 , 2-7 1 , 3-7 42 to 3-8 days 43 . Abstinence of long period is associated with an increase in dead and abnormal shaped cells 44 and fall in semen quality 45 .…”
Section: Discussionmentioning
confidence: 85%
“…66,67 Though the effects of prolonged abstinence on semen quality are inconclusive it is recommended not to exceed 10 days of abstinence as it could affect semen performance negatively thus undermining the fertility potential. [67][68][69]…”
Section: Sperm Function Is Better After a Long Period Of Abstinence (...mentioning
confidence: 99%